1) (x+y)+(x+y)²=(x+y)(1*x+y)
2) (a-b)²+a-b=(a-b)(a-b+1)
3) 2m (m-n)+ (m-n)²=(m-n)(2m+m-n)=(m-n)(3m-n)
4) 4q(p-1)+(p-1)²=(p-1)(4q+p-1)
5) a(x-c)+bc-bx=ax-ac-bc-bx=a(x-c)-b(-c+x)=(x-c)(a-b)
6) a(b+c) +db+dc=ab+ac+db+dc=a(b+c)+d(b+c)=(b+c)(a+d)
7) 3a(2b+c) +8b+4c=3a(2b+c)+4(2b+c)=(2b+c)(3a+4)
8) 2x(3x-4y)-6x+8y=2x(3x-4y)-2(3x-4y)=(3x-4y)(2x-2)=(3x-4y)*2(x-1)=
=2(3x-4y)(x-1)
1) (x+y)+(x+y)²=(x+y)(1*x+y)
2) (a-b)²+a-b=(a-b)(a-b+1)
3) 2m (m-n)+ (m-n)²=(m-n)(2m+m-n)=(m-n)(3m-n)
4) 4q(p-1)+(p-1)²=(p-1)(4q+p-1)
5) a(x-c)+bc-bx=ax-ac-bc-bx=a(x-c)-b(-c+x)=(x-c)(a-b)
6) a(b+c) +db+dc=ab+ac+db+dc=a(b+c)+d(b+c)=(b+c)(a+d)
7) 3a(2b+c) +8b+4c=3a(2b+c)+4(2b+c)=(2b+c)(3a+4)
8) 2x(3x-4y)-6x+8y=2x(3x-4y)-2(3x-4y)=(3x-4y)(2x-2)=(3x-4y)*2(x-1)=
=2(3x-4y)(x-1)